Hubungan Stress dan Indeks Masa Tubuh (IMT) dengan Kejadian Dismenorea di SMKS Keluarga Bunda Jambi Tahun 2022 - Silvia Mariana; Rika Ulan Dari (Universitas Batanghari Jambi, 2023)
Dysmenorrhea is a common complaint among women of reproductive age, including adolescents, about 50% of women in the world experience dysmenorrhea. Many factors can cause dysmenorrhea, one of which is stress and body mass index (BMI). This study aims to determine the relationship between stress and body mass index with the incidence of dysmenorrhea. This study used a cross sectional design. The population in this study were all female students in grades X and XI who attended SMKS Keluarga Bunda, totaling 80 people with a sampling technique, namely a total sampling of 80 people by distributing questionnaires and then measuring height and weight. The results showed that there was a relationship between stress and body mass index with dysmenorrhoea, with p-value <0.05. Stress and BMI are closely related to the incidence of dysmenorrhea. It is hoped that adolescents will have more attention to BMI and factors that influence BMI such as food intake in order to prevent dysmenorrhea and are expected to avoid or control stress by having a positive attitude and mindset.